Pengaruh Brand Image Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembeli Air Minum Dalam Kemasan Merek Cleo - Nuning Nurna Dewi (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2021)
This study aims to determine whether the brand image, price and product quality have a significant effect on purchasing decisions for bottled drinking water. The research method used is a quantitative approach, with data collection techniques in the form of a questionnaire. The population in this study were all consumers of bottled drinking water with the CLEO brand in Karangandong village, Driyorejo sub-district, Gresik district, who made purchasing decisions. The sampling technique used purposive sampling with a probability method with a specified sample size of 100 people. The data analysis technique used is multiple linear regression. The hypothesis test in this study shows that the three independent variables have a significant effect on the dependent variable. This is evidenced by the t value of the brand image variable of 2.410 with a significant value of 0.018, then the t value of the price variable of 4.104 with a significant value of 0.000, and evidence of the t value of the variable product quality of 3.287 has a significant effect of 0.001. Brand image, price and product quality have a significant positive effect on purchasing decisions. This is evidenced by the calculated F value of 15,349 with a significant amount of 0,000.